Ketersediaan Handrub Meningkatkan Kebiasaan Cuci Tangan Ibu Rumah Tangga - Desy Ardiyati; Linda Suwarni; Abduh Ridha (Politeknik Kesehatan Kemenkes Mamuju, 2021)
Diarrheal disease is a problem of public health that is still occurring in Indonesia, especially in children because of morbidity and mortality is still very high. Hand washing is one of the prevention factors of diarrhoea disease but the habit of hand washing habits is still low. Pontianak City is in the first position of 14 districts/cities for diarrhea cases that are handled according to gender in West Kalimantan province. Pontianak City Health Office report year 2015 diarrhea pain figure of 22.24 per 1000 inhabitants. The aim of this study is to determine the effectiveness of the use of handrub on the habit of washing housewives in the work area Alianyang Pontianak City. The result showed that there is a significant increase in housewives hand washing behaviors that support 44.4% increase to 55.6% in experimental groups with (p value = 0.000). Based on the results of research and discussion, it can be concluded that the use of handrub is effective against the behavior of housewives' hand washing because there is a meaningful difference between before and after using handrub.